The perspective and experiences of significant others on electroconvulsive therapy - Pieter-Jan Geerts; Pieter-Jan Geerts; Souad Abihi; Nele Van De Velde; Chris Baeken; Chris Baeken; Chris Baeken; Chris Baeken; Chris Baeken; Gilbert Lemmens; Gilbert Lemmens; Sofie Verhaeghe; et al. (Frontiers in Psychiatry)
IntroductionElectroconvulsive therapy (ECT) is an essential but often controversial treatment in psychiatry. While existing research focuses on patient outcomes, the perspectives of significant others (SOs) remain underexplored. They play, nevertheless, a crucial role in decision-making, treatment adherence, and post-treatment evaluation. To better understand their perceptions, challenges, and support needs, this study aims to explore the lived experiences of SOs and ECT.MethodsA qualitative phenomenological approach was employed using semi-structured interviews with nine SOs of patients who underwent ECT. Thematic analysis was conducted using Braun and Clarke’s framework, and data were analyzed using the NVivo software.ResultsBefore ECT, SOs experienced a significant emotional burden, describing their lives as unlivable due to the patients’ severe illness. The decision to start ECT was marked by feelings of responsibility and fear but also driven by hope. During ECT, SOs closely monitored treatment effects and side effects, balancing improvements against challenges such as memory loss and fatigue. The psychiatrist played a central role in shaping perceptions and instilling hope. During the maintenance phase, SOs faced logistical challenges and stigma but aimed to integrate ECT into daily life while supporting patient autonomy.ConclusionThis study highlights the complex role of SOs in ECT. Unlike previous studies that have focused on caregiver burden, it emphasizes the role of hope in decision-making and treatment adherence. SOs value transparent communication from psychiatrists and seek structured support systems to navigate practical and emotional challenges. Stigma remains a significant barrier to open discussion and social integration.